CYPome of the conifer pathogen Heterobasidion irregulare: Inventory, phylogeny, and transcriptional analysis of the response to biocontrol. Issue 2 (February 2017) - Mgbeahuruike, Anthony C.; Kovalchuk, Andriy; Ubhayasekera, Wimal; Nelson, David R.; Yadav, Jagjit S.
Abstract: The molecular mechanisms underlying the interaction of the pathogen, Heterobasidion annosum s.l., the conifer tree and the biocontrol fungus, Phlebiopsis gigantea have not been fully elucidated. Members of the cytochrome P450 (CYP) protein family may contribute to the detoxification of components of chemical defence of conifer trees by H. annosum during infection. Additionally, they may also be involved in the interaction between H. annosum and P. gigantea . A genome-wide analysis of CYPs in Heterobasidion irregulare was carried out alongside gene expression studies. According to the Standardized CYP Nomenclature criteria, the H. irregulare genome has 121 CYP genes and 17 CYP pseudogenes classified into 11 clans, 35 families, and 64 subfamilies. Tandem CYP arrays originating from gene duplications and belonging to the same family and subfamily were found. Phylogenetic analysis showed that all the families of H. irregulare CYPs were monophyletic groups except for the family CYP5144. Microarray analysis revealed the transcriptional pattern for 130 transcripts of CYP-encoding genes during growth on culture filtrate produced by P. gigantea . The high level of P450 gene diversity identified in this study could result from extensive gene duplications presumably caused by the high metabolic demands of H. irregulare in its ecological niches. Highlights: Heterobasidion irregulare genome has 122 CYP genes. The CYPs were classified into 11 clans, 35 families and 64 subfamilies. The largest cluster was on scaffold 5 in subfamily M (CYP5144). Microarray analysis identified 130 transcripts of P450 encoding genes. The H. irregulare CYPs showed different expression patterns.